Preparation method of polymer fiber with superfine fiber growing on surface
By using melt blended spinning and ultrasonic oscillation methods during the fiber preparation process, the limitations of the fiber fiber opening method in the prior art are solved, and the ultrafine fibers are formed on the fiber surface, which improves the insulation, compression elasticity and frictional properties of the fibers.
Patent Information
- Application Number
- CN202510316243.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
In the prior art, the two-component fiber fiber opening method has limitations such as high mechanical energy consumption, chemical solvent pollution, and thermal energy damages material performance, making it difficult to meet specific application needs.
The polymer fibers with surface growth of microfiber fibers were prepared by mixing the matrix phase polymer and the dispersed phase polymers and then ultrasonic shocks the spinned fibers.
A large number of microfibers with densely distributed distribution are achieved on the fiber surface, which significantly improves the thermal insulation, compression elasticity and frictional properties of the fiber.
Smart Images

Figure CN119843384A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber materials and relates to a method for preparing polymer fibers with ultrafine fibers grown on the surface. Background Art
[0002] At present, research is on the preparation and application of bicomponent fibers, including orange-skin fibers and sea-island fibers. These fibers can form ultrafine fiber structures on the surface of the matrix fibers through a specific spinning process, thereby improving the performance of the material. However, due to the weak degree of fiber cracking, the comprehensive performance of the bicomponent materials formed only by the spinning process cannot meet the needs of some specific applications. The bicomponent ultrafine fibers need to be opened to obtain finer fiber morphology and more delicate fiber structure. The fiber opening methods can be mainly divided into three categories: mechanical fiber opening, chemical solvent fiber opening, and thermal fiber opening. However, each of these methods has certain limitations. For example, mechanical fiber opening consumes a lot of energy; chemical fiber opening pollutes the environment; and thermal fiber opening damages the performance of the material itself.
[0003] For example, patent CN 114717749 A treats Lyocell fiber and another fiber material by water spunlace, and then treats them with sodium hydroxide solution for ultrasonic and stirring treatment respectively, to prepare water spunlace nonwoven material containing brush structure micro / nano fiber. Patent CN 107217512 A uses mechanical method to pre-treat para-aramid to roughen its fiber surface, or adjusts the processing technology to improve the internal structure of the fiber, reduce the density of the fiber surface, and produce fibrillation or pore-like structure. Patent CN 105926272 A pre-treats Lyocel11 fiber fabric, then puts it into concentrated alkali solution, stirs and soaks it, obtains Lyocel11 fiber fabric after swelling treatment, removes the concentrated alkali solution, and then treats it by ultrasonic treatment, washing and drying, grinding treatment, and using the cavitation effect of ultrasonic waves in the liquid medium as an external force to uniformly treat Lyocel11 fiber products, which can make Lyocel11 fiber produce uniform fibrillation effect faster. However, the use of solvents will have a certain degree of impact on both the human body and the environment.
[0004] Therefore, it is of great significance to study a method for preparing polymer fibers with ultrafine fibers grown on the surface to solve the problems existing in the prior art. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing polymer fibers with ultrafine fibers grown on the surface.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a polymer fiber with ultrafine fibers grown on the surface, comprising: mixing a matrix phase polymer and a dispersed phase polymer to obtain a mixture, and then performing melt blending spinning, and then performing ultrasonic vibration on the spun fiber to obtain the polymer fiber with ultrafine fibers grown on the surface;
[0008] The matrix phase polymer is polypropylene (PP), and the dispersed phase polymer is PE, PBT, PET or PTT;
[0009] The proportion of dispersed phase polymer in the mixture is 30~50wt%;
[0010] The ratio of the zero shear viscosity (viscosity when the shear rate is 0) of the dispersed phase polymer to the matrix phase polymer ranges from 0.01 to 1.
[0011] As the preferred technical solution:
[0012] In the method for preparing a polymer fiber with surface-grown ultrafine fibers as described above, the zero shear viscosity of the matrix phase polymer at the spinning temperature is 50~20000 Pa·s, the zero shear viscosity of the dispersed phase polymer at the spinning temperature is 50~1200 Pa·s, and the spinning temperature is 200~310°C.
[0013] In the method for preparing a polymer fiber with surface-grown ultrafine fibers, the interfacial tension between the dispersed phase polymer and the matrix phase polymer is not less than 0.5×10 -3 N / m. Polymer blends with low interfacial adhesion strength are prone to interfacial debonding, leading to the extreme case of interfacial separation on the fiber surface - microfiber separation, while incompatible polymer blends with high interfacial adhesion strength are conducive to forming a surface with limited interfacial separation, thereby producing deep grooves. Generally speaking, the lower the interfacial tension, the more conducive it is to contact between the two phases, which can make the molecules of the two phases closer to each other, thereby increasing the chance of interaction between molecules and helping to improve the interfacial adhesion strength.
[0014] In the method for preparing a polymer fiber with ultrafine fibers grown on the surface, during melt blending and spinning, the melt extrusion speed is 2.5×10 -11 ~1.5×10 -8 m 3 / s, the drawing ratio is 3.0~5.0, the drawing temperature is 80~160℃, and the spinning speed is above 16m / min.
[0015] In the preparation method of a polymer fiber with surface-grown ultrafine fibers as described above, the aspect ratio of the spinneret hole is 3.0~6.0. The aspect ratio of the spinneret hole used in spinning has a significant effect on the surface morphology of the blended fiber. If the aspect ratio is relatively small, the residence time of the melt in the spinneret hole is short, the shearing effect is relatively weak, the orientation degree is low, and the surface of the extruded blended fiber is rough, and more irregular protrusions, depressions or uneven thickness may appear, and there may even be surface defects caused by melt fracture. If the aspect ratio is relatively large, the shearing and stretching effects on the melt in the spinneret hole are enhanced, the residence time is increased, and the orientation degree and uniformity of the melt are improved, which helps to form a smoother and more uniform fiber surface and reduce surface defects. However, if the aspect ratio is too large, the melt pressure drop increases, which is easy to cause extrusion instability, and may also affect the fiber surface quality. In actual production, it is also easily affected by the matrix and processing conditions.
[0016] In the method for preparing a polymer fiber with ultrafine fibers grown on the surface as described above, the power of ultrasonic oscillation is 300-500W and the time is 30-120 min.
[0017] The method for preparing a polymer fiber with ultrafine fibers grown on the surface as described above, wherein the diameter of the polymer fiber with ultrafine fibers grown on the surface is 5×10 -5 ~8×10 -5 m, the diameter of the ultrafine fiber is 2×10 -6 ~8×10 -6 m.
[0018] Principle of the invention:
[0019] Generally, when the zero shear viscosity ratio of the dispersed phase polymer to the matrix phase polymer is between 0.01 and 1, the droplets are most likely to break. In the capillary, the low-viscosity dispersed phase always tends to migrate to the place with high shear rate. During the spinning process, this phenomenon causes the dispersed phase to migrate more to the fiber surface, resulting in irregular protrusions on the fiber surface. With the increase of the dispersed phase content, the droplet-shaped dispersed phase increases, and the surface of the blended fiber also presents a large number of irregularly distributed protrusions with varying heights. When the dispersed phase content further increases to 30%, long and short microfibers coexist inside the fiber, and the fiber surface has more long microfibers with strip-like protrusions. After ultrasonic oscillation, a large number of densely distributed ultrafine fibers are finally formed on the surface of the matrix fiber. The reason why a large number of densely distributed ultrafine fibers are formed on the surface of the matrix fiber after ultrasonic oscillation is that the cavitation effect generated when the ultrasonic wave propagates in the liquid medium produces a strong microjet that impacts and shears the fiber surface, destroys some relatively weak connections between the fibrils inside the blended fiber, and promotes the splitting of fine fibers on the fiber surface, showing the characteristics of ultrafine fibers.
[0020] As the content of the dispersed phase increases, the dispersed phase is extremely easy to coalesce and form large droplets. As the content of the dispersed phase increases, the probability of its collision during the melt processing increases, and the probability of coalescing to form large droplets increases accordingly. According to the capillary theory, large droplets can have greater deformation ability. An incompatible blend system will form a typical sea-island structure, in which the dispersed phase is the island phase and the continuous phase is the sea phase. When the composition of the two blending components remains unchanged, the determination of the island phase and the sea phase depends on the component viscosity and the ratio of the two components. In most cases, the phase with a higher viscosity will form an island phase, and the phase with a lower viscosity will form a sea phase; the phase with a lower viscosity will form an island phase, and the phase with a higher viscosity will form a sea phase. When the viscosity ratio of the dispersed phase polymer to the matrix phase polymer is >1, the dispersed phase may be distributed in the matrix and it is difficult to migrate to the surface, and the fiber surface presents a smooth morphology. If the content of the dispersed phase is >50%, the distribution of the dispersed phase and the matrix will change. Specifically, in incompatible polymer blends, according to the general theory of phase transition and a large number of experimental studies, when the volume fraction of the dispersed phase gradually increases and exceeds 50%, the interaction and spatial distribution state between the dispersed phase particles will change significantly. The probability of the dispersed phase particles contacting and connecting with each other is greatly increased, and the original continuous phase may be divided into discontinuous parts by the dispersed phase, thereby transforming the dispersed phase into the continuous phase, forming the so-called "phase reversal" phenomenon, and the viscosity ratio changes accordingly.
[0021] The thermal insulation, compression resilience and friction performance of polymer fibers with ultrafine fibers grown on the surface are significantly improved, as follows:
[0022] Improved thermal insulation: After a large number of densely distributed ultrafine fibers are formed, the air between the fibers is divided into many tiny air chambers. The air in these air chambers is not easy to flow, and air is a poor conductor of heat, which can effectively hinder the transfer of heat through air convection, thereby enhancing thermal insulation performance. At the same time, ultrafine fibers have a large specific surface area. When exchanging heat with the outside world, more fiber surface can absorb and store heat, reducing heat loss.
[0023] Improved compression resilience: The addition of ultrafine fibers increases the flexibility and deformability of the fiber assembly. When subjected to compression, the ultrafine fibers can slide and bend relative to the matrix fibers, dispersing the pressure, making the fiber assembly more able to withstand compression without excessive damage. Moreover, the ultrafine fibers themselves have a certain elastic recovery ability, which can help the fiber assembly quickly return to its original shape after the pressure is removed, thereby improving the compression resilience.
[0024] Improved friction performance: A large number of dense microfibers increase the roughness and contact area of the fiber surface. When in contact with other objects, more fibers interact with the surface of the object, generating more friction. At the same time, the flexibility of the microfibers enables them to better fit the contact surface during the friction process, increasing the effective effect of friction, thereby improving friction performance.
[0025] In some applications, such as when textile fabrics are used to make gloves, improved friction properties can make the gloves better grip objects, less likely to slip, and improve the safety and accuracy of operations. For some fiber products that need to remain in a fixed position, such as fillings, carpets, cushions, etc., good friction properties can make them less likely to slide during use, increasing stability and comfort. In addition, higher friction properties mean that the fiber surface can better resist wear when rubbing against other objects, extending the service life of fiber products and reducing damage and deformation caused by friction.
[0026] Beneficial effects:
[0027] (1) The present invention provides a method for preparing a polymer fiber with ultrafine fibers grown on the surface. An incompatible polymer is formed by adding a dispersed phase into a matrix, and microfibers are formed on the surface of the matrix fiber by a melt blending method. The process is simple and does not require solvent treatment. The microfibers are then deformed into ultrafine fibers by ultrasonic vibration, thereby obtaining a large number of ultrafine fibers on the matrix fiber, forming a structure in which ultrafine fibers are entangled on the matrix, which is used in ultrafine fiber applications such as down.
[0028] (2) The present invention provides a method for preparing a polymer fiber with ultrafine fibers grown on the surface. The prepared polymer fiber with ultrafine fibers grown on the surface has significantly improved thermal insulation, compression resilience and friction performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The surface temperature variation diagram of different samples before and after ultrasound in Example 1;
[0030] Figure 2 are the zero shear viscosity of the matrix phase polymer, the zero shear viscosity of the dispersed phase polymer, and the zero shear viscosity ratio of the dispersed phase polymer to the matrix phase polymer at different temperatures in Example 1, and the horizontal line in the middle of the figure indicates that the viscosity ratio is 1;
[0031] Figure 3 The surface morphology of the 30% blended fiber treated with ultrasonic vibration at different times in Example 1 are (a) 30min, (b) 60min, (c) 90min, and (d) 120min;
[0032] Figure 4 The system surface structure morphology of the polymer fibers of Comparative Examples 1 to 6;
[0033] Figure 5 The system surface structure morphology of the polymer fibers of Comparative Examples 7 to 11 and Example 1;
[0034] Figure 6 This is a system surface structure morphology diagram of the polymer fiber of Comparative Example 12. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0036] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0037] (1) Fiber compression rebound performance:
[0038] The oil on the fiber surface was cleaned with ethanol solution and air-dried at room temperature. The fibers were cut into short fibers with a length of 30-50 mm, and the same mass of loose fibers were weighed and put into a non-woven bag (sample bag) with a size of 6 cm × 6 cm to ensure that the fibers were evenly distributed. The KES-G5 compression tester was used to test the samples that had been humidified for 24 hours. The size of the circular probe was 2 cm 2 Each sample was tested three times and the results were averaged.
[0039] The calculation formula is as follows:
[0040] WC ;
[0041] W ;
[0042] ;
[0043] ;
[0044] Where WC is the compression work, T0 is the sample thickness, T m is the maximum pressure p m The thickness of the sample under the pressure, T is the thickness of the compressed sample bag, p is the pressure per unit area of the sample bag during compression, p' is the pressure per unit area of the sample bag during compression recovery, W is the compression recovery work, RC is the compression recovery rate, and LC is the linearity of the compression curve.
[0045] The greater the compression work, the fluffier it is. The compression work recovery rate RC represents the compression elasticity and recovery performance of the sample. The larger the value, the better the compression recovery ability of the fabric.
[0046] The linearity LC of the compression curve indicates the degree of buckling of the compression curve of the specimen. The larger the value, the easier it is for compression deformation to occur.
[0047] (2) Friction performance:
[0048] The dynamic friction of different blended fibers in the fiber-metal roller friction mode was measured using a fiber friction coefficient tester at a temperature of 25 °C and a relative humidity of 65%, and the friction coefficient was obtained. The steel roller speed was 30 r / min, and the tension applied to the single fiber was 0.2 cN. The experiment was repeated 3 to 5 times and the average value was taken.
[0049] (3) Thermal insulation performance:
[0050] Clean the oil on the fiber surface with ethanol solution and air dry at room temperature. Cut the fiber into short fibers with a length of 30-50 mm, and weigh the same mass of loose fibers and put them into a non-woven bag (sample bag). The size of the sample bag is 6 cm × 6 cm, so that the fibers are evenly distributed. Put the sample bags with different filling samples on the hot stage, start timing the moment they are put on, and use an infrared imager to record the changes in the surface temperature of the sample bag over time for 30 minutes. Set the hot stage to 37°C; take 3-5 points and calculate the average value. The ambient temperature is 20°C and the relative humidity is 50%.
[0051] Example 1
[0052] A method for preparing a polymer fiber with ultrafine fibers grown on the surface, the specific steps are as follows:
[0053] (1) Preparation of raw materials;
[0054] Matrix phase polymer: polypropylene, zero shear viscosity at 200°C is 18000 Pa·s, number average molecular weight is 250000, and molecular weight distribution index is 3.3;
[0055] Dispersed phase polymer: PE, zero shear viscosity at 200°C is 1100 Pa·s, number average molecular weight is 120000, and molecular weight distribution index is 2.1;
[0056] Figure 2 The zero shear viscosity ratio of the dispersed phase polymer to the matrix phase polymer at different temperatures is shown in Figure 2. It can be seen that the viscosity of the dispersed phase is lower than that of the matrix under the same test conditions, and the zero shear viscosity ratio of the system is <1.
[0057] The interfacial tension between the dispersed phase polymer and the matrix phase polymer is 4.3×10-3 N / m;
[0058] (2) The matrix phase polymer and the dispersed phase polymer are mixed to obtain a mixture, which is blended and granulated using a twin-screw extruder, and then cooled in a water bath at room temperature (25°C), and then cut using a pelletizer to obtain blended slices; subsequently, the blended slices are placed in a constant temperature hot air oven at 100°C for drying for 24 hours;
[0059] Among them, the proportion of dispersed phase polymer in the mixture is 30wt%;
[0060] (3) melt-blending and spinning the product of step (2), followed by cooling, drawing and heat setting in sequence, and then immersing the obtained fiber in an ice water bath and ultrasonically vibrating at a power of 500 W for 30 min, and finally drying in a constant temperature hot air oven at 60° C. for 4 h to obtain a polymer fiber with ultrafine fibers grown on the surface;
[0061] During melt blending spinning, the melt extrusion speed is 7.8×10 -9 m 3 / s, air cooling temperature is 20℃, draft ratio is 3, draft temperature is 80℃, spinning temperature is 200℃, spinning speed is 16m / min, spinneret hole aspect ratio is 3, heat setting temperature is 120℃;
[0062] The final surface-grown ultrafine fiber has a polymer fiber diameter of 6.5×10 -5 m, and the diameter of the ultrafine fiber is 2.4×10 -6 m, the friction coefficient of the polymer surface with ultrafine fibers grown on the surface is 0.075, and the temperature change rate is 0.0039℃ / s.
[0063] The compression properties of the fibers before and after ultrasonic vibration are shown in Table 1. It can be found that the fluffy properties of the blended fibers are significantly improved after ultrasonic vibration.
[0064] Table 1
[0065] Sample <![CDATA[T0(mm)]]> <![CDATA[T m (mm)]]> <![CDATA[WC((gf·cm) / cm 2 )]]> RC (%) LC Before ultrasound 4.976 2.183 11.934 34.03 0.253 After ultrasound 9.226 3.259 35.149 49.08 0.224
[0066] Figure 1 The figure shows the change of the surface temperature of the sample bag at different times. At the moment of placing it on the hot stage, the temperature rises rapidly with the passage of time. After a certain period of time, the temperature change no longer rises sharply, and changes slowly until it is basically stable. By comparison, it is found that the temperature change rate of the fiber before ultrasound is 0.0047℃ / s within 30 minutes, and the temperature change rate of the fiber after ultrasound is 0.0039℃ / s. It can be seen that the thermal resistance of the fiber after ultrasound is higher than that of the fiber before ultrasound, which shows that the thermal insulation performance is also better than the pre-ultrasonic blended fiber.
[0067] Figure 3The 30% surface morphology of the blended fiber in Example 1 at different ultrasonic vibration treatment times is shown. By subjecting the blended fiber to ultrasonic vibration treatment for different times, it can be seen that microfibers of varying degrees appear on the surface of the blended fiber. When the ultrasonic time is 30 minutes, the ultrafine fibers are distributed on the fiber in a dispersed manner. As the ultrasonic time increases, the microfibers and ultrafine fibers that were originally dispersed are re-entangled on the matrix fiber. The reason is that the longer the ultrasonic time, the higher the water temperature and the greater the force, causing the ultrafine fibers to shrink and attach to the main fiber.
[0068] Comparative Examples 1 to 6
[0069] A method for preparing polymer fibers is basically the same as that of Example 1, except that the proportions of dispersed phase polymer in the mixture in step (3) are 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% and 30 wt%, respectively, and ultrasonic vibration is not performed.
[0070] like Figure 4 As shown, when the component ratio of the added dispersed phase is between 5 and 30 wt %, before ultrasonic vibration, when the added amount is less than 30%, only rough structures of varying degrees appear on the fiber surface, and ultrafine fiber structures appear at 30%.
[0071] Comparative Examples 7-11
[0072] A method for preparing a polymer fiber is basically the same as that of Example 1, except that the proportion of the dispersed phase polymer in the mixture in step (3) is 5wt%, 10wt%, 15wt%, 20wt% and 25wt% respectively.
[0073] like Figure 5 As shown, the component ratio of the dispersed phase added in Comparative Examples 7 to 11 and Example 1 is 5 to 30 wt %. After ultrasonic vibration, when the added amount is less than 30 wt %, there is no obvious change on the fiber surface, and a large number of ultrafine fiber structures appear at 30 wt % (ie, Example 1).
[0074] Comparative Example 12
[0075] A method for preparing a polymer fiber is basically the same as Example 1, except that the zero shear viscosity of the matrix phase polymer at the spinning temperature (200°C) is 300 Pa·s, and the zero shear viscosity of the dispersed phase polymer at the spinning temperature (200°C) is 400 Pa·s, that is, the zero shear viscosity ratio of the dispersed phase polymer to the matrix phase polymer is 1.3, and the proportion of the dispersed phase polymer in the mixture in step (3) is 5wt%.
[0076] like Figure 6 As shown, after ultrasonic vibration, the surface of the polymer fiber finally obtained has no ultrafine fiber structure.
[0077] Comparative Example 13
[0078] A method for preparing a polymer fiber is basically the same as that of Example 1, except that the proportion of the dispersed phase polymer in the mixture in step (3) is 55 wt %.
[0079] The surface of the finally prepared polymer fiber has no ultrafine fiber structure.
[0080] Example 2
[0081] A method for preparing a polymer fiber with ultrafine fibers grown on the surface, the specific steps are as follows:
[0082] (1) Preparation of raw materials;
[0083] Matrix phase polymer: polypropylene, zero shear viscosity at 250°C is 1700 Pa·s, number average molecular weight is 200000, and molecular weight distribution index is 3.2;
[0084] Dispersed phase polymer: PBT, zero shear viscosity at 250°C is 400 Pa·s, number average molecular weight is 30,000, and molecular weight distribution index is 3;
[0085] The interfacial tension between the dispersed phase polymer and the matrix phase polymer is 8.3×10 -3 N / m;
[0086] (2) The matrix phase polymer and the dispersed phase polymer are mixed to obtain a mixture, which is blended and granulated using a twin-screw extruder, and then cooled in a room temperature water bath, and then cut using a pelletizer to obtain blended slices; subsequently, the blended slices are placed in a 120° C. constant temperature hot air oven for drying for 48 h;
[0087] Among them, the proportion of dispersed phase polymer in the mixture is 40wt%;
[0088] (3) melt-blending and spinning the product of step (2), followed by cooling, drawing and heat setting in sequence, and then immersing the obtained fiber in an ice water bath and ultrasonically vibrating at a power of 450 W for 60 min, and finally drying in a constant temperature hot air oven at 60° C. for 4 h to obtain a polymer fiber with ultrafine fibers grown on the surface;
[0089] During melt blending spinning, the melt extrusion speed is 7.8×10 -9 m 3 / s, air cooling temperature is 20℃, drawing ratio is 3.5, drawing temperature is 80℃, spinning temperature is 250℃, spinning speed is 16m / min, aspect ratio of spinneret hole is 3:1, heat setting temperature is 120℃;
[0090] The final surface-grown ultrafine fiber has a polymer fiber diameter of 6.3×10 -5 m, the diameter of the ultrafine fiber is 3.6×10-6m, the surface friction coefficient of the polymer fiber on which the ultrafine fiber is grown is 0.068, and the temperature change rate is 0.0039℃ / s.
[0091] The compression properties of the fibers before and after ultrasonic vibration are shown in Table 2 below. It can be found that the fluffy properties of the blended fibers are significantly improved after ultrasonic vibration.
[0092] Table 2
[0093] Sample <![CDATA[T0(mm)]]> <![CDATA[T m (mm)]]> <![CDATA[WC((gf·cm) / cm 2 )]]> RC (%) LC Before ultrasound 4.150 1.357 11.108 33.20 0.190 After ultrasound 8.477 2.510 34.400 48.26 0.208
[0094] Example 3
[0095] A method for preparing a polymer fiber with ultrafine fibers grown on the surface, the specific steps are as follows:
[0096] (1) Preparation of raw materials;
[0097] Matrix phase polymer: polypropylene, zero shear viscosity at 280°C is 450 Pa·s, number average molecular weight is 150,000, and molecular weight distribution index is 3;
[0098] Dispersed phase polymer: PET, zero shear viscosity at 280°C is 300 Pa·s, number average molecular weight is 20,000, and molecular weight distribution index is 1.8;
[0099] The interfacial tension between the dispersed phase polymer and the matrix phase polymer is 11.5×10 -3 N / m;
[0100] (2) The matrix phase polymer and the dispersed phase polymer are mixed to obtain a mixture, which is blended and granulated using a twin-screw extruder, and then cooled in a room temperature water bath, and then cut using a pelletizer to obtain blended slices; subsequently, the blended slices are placed in a constant temperature hot air oven at 150° C. for drying for 48 hours;
[0101] Among them, the proportion of dispersed phase polymer in the mixture is 45wt%;
[0102] (3) melt-blending and spinning the product of step (2), followed by cooling, drawing and heat setting in sequence, and then immersing the obtained fiber in an ice water bath and ultrasonically vibrating at a power of 400 W for 90 min, and finally drying in a constant temperature hot air oven at 60° C. for 4 h to obtain a polymer fiber with ultrafine fibers grown on the surface;
[0103] During melt blending spinning, the melt extrusion speed is 7.8×10 -9 m 3 / s, air cooling temperature is 20℃, draft ratio is 4, draft temperature is 80℃, spinning temperature is 280℃, spinning speed is 16m / min, aspect ratio of spinneret hole is 3:1, heat setting temperature is 130℃;
[0104] The final surface-grown ultrafine fiber has a polymer fiber diameter of 5.2×10 -5 m, and the diameter of the ultrafine fiber is 5.7×10 -6 m, the surface friction coefficient of the polymer fiber with ultrafine fibers grown on the surface is 0.094, and the temperature change rate is 0.0036℃ / s.
[0105] The compression properties of the fibers before and after ultrasonic vibration are shown in Table 3 below. It can be found that the fluffy properties of the blended fibers are significantly improved after ultrasonic vibration.
[0106] Table 3
[0107] Sample <![CDATA[T0(mm)]]> <![CDATA[T m (mm)]]> <![CDATA[WC((gf·cm) / cm 2 )]]> RC (%) LC Before ultrasound 3.917 1.124 10.875 31.986 0.177 After ultrasound 8.221 2.254 34.144 45.28 0.214
[0108] Example 4
[0109] A method for preparing a polymer fiber with ultrafine fibers grown on the surface, the specific steps are as follows:
[0110] (1) Preparation of raw materials;
[0111] Matrix phase polymer: polypropylene, zero shear viscosity at 300°C is 400 Pa·s, number average molecular weight is 130,000, and molecular weight distribution index is 3.1;
[0112] Dispersed phase polymer: PTT, zero shear viscosity at 300°C is 350 Pa·s, number average molecular weight is 25000, and molecular weight distribution index is 2.2;
[0113] The interfacial tension between the dispersed phase polymer and the matrix phase polymer is 14.8×10 -3 N / m;
[0114] (2) The matrix phase polymer and the dispersed phase polymer are mixed to obtain a mixture, which is blended and granulated using a twin-screw extruder, and then cooled in a room temperature water bath, and then cut using a pelletizer to obtain blended slices; subsequently, the blended slices are placed in a constant temperature hot air oven at 160° C. for drying for 48 hours;
[0115] Among them, the proportion of dispersed phase polymer in the mixture is 50wt%;
[0116] (3) melt-blending and spinning the product of step (2), followed by cooling, drawing and heat setting in sequence, and then immersing the obtained fiber in an ice water bath and ultrasonically vibrating at a power of 300 W for 120 min, and finally drying in a constant temperature hot air oven at 60° C. for 4 h to obtain a polymer fiber with ultrafine fibers grown on the surface;
[0117] During melt blending spinning, the melt extrusion speed is 7.8×10 -9 m 3 / s, air cooling temperature is 20℃, draft ratio is 5, draft temperature is 80℃, spinning temperature is 300℃, spinning speed is 16m / min, aspect ratio of spinneret hole is 3:1, heat setting temperature is 150℃;
[0118] The final surface-grown ultrafine fiber has a polymer fiber diameter of 7.9×10 -5 m, the diameter of the ultrafine fiber is 6.5×10 -6 m, the surface friction coefficient of the polymer fiber with ultrafine fibers grown on the surface is 0.088, and the temperature change rate is 0.0038℃ / min.
[0119] The compression properties of the fibers before and after ultrasonic vibration are shown in Table 4 below. It can be found that the fluffy properties of the blended fibers are significantly improved after ultrasonic vibration.
[0120] Table 4
[0121] Sample <![CDATA[T0(mm)]]> <![CDATA[T m (mm)]]> <![CDATA[WC((gf·cm) / cm 2 )]]> RC (%) LC Before ultrasound 4.17 1.425 11.532 33.720 0.192 After ultrasound 8.823 2.310 32.579 47.72 0.224
Claims
1. A method for preparing a polymer fiber with ultrafine fibers grown on the surface, characterized in that: The matrix phase polymer and the dispersed phase polymer are mixed to obtain a mixture, and then melt-blended and spun, and then the spun fibers are subjected to ultrasonic vibration to obtain polymer fibers with ultrafine fibers grown on the surface; The matrix phase polymer is polypropylene, and the dispersed phase polymer is PE, PBT, PET or PTT; The proportion of dispersed phase polymer in the mixture is 30~50wt%; The zero shear viscosity ratio of the dispersed phase polymer to the matrix phase polymer ranges from 0.01 to 1.
2. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 1, characterized in that: The zero shear viscosity of the matrix phase polymer at the spinning temperature is 50~20000 Pa·s, the zero shear viscosity of the dispersed phase polymer at the spinning temperature is 50~1200 Pa·s, and the spinning temperature is 200~310 ℃.
3. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 2, characterized in that: The interfacial tension between the dispersed phase polymer and the matrix phase polymer is not less than 0.5×10 -3 N / m.
4. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 1, characterized in that: During melt blending spinning, the melt extrusion speed is 2.5×10 -11 ~1.5×10 -8 m 3 / s, the drawing ratio is 3.0~5.0, the drawing temperature is 80~160℃, and the spinning speed is above 16m / min.
5. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 1, characterized in that: The aspect ratio of the spinneret hole is 3.0~6.
0.
6. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 1, characterized in that: The power of ultrasonic oscillation is 300~500W, and the time is 30~120 min.
7. The method for preparing a polymer fiber with surface-grown ultrafine fibers according to claim 1, characterized in that: The diameter of the polymer fiber grown on the surface is 5×10 -5 ~8×10 -5 m, the diameter of the ultrafine fiber is 2×10 -6 ~8×10 -6 m.
Citation Information
Patent Citations
Preparation method of superfine-velvet Lyocell fiber fabric
CN105926272A
Method for increasing dyeing depth of para-aramid fibers and fabrics
CN107217512A
Preparation method of polyester fiber with special surface structure
CN112281229A
Hydroxyl polypropylene copolymer fiber with surface concave-convex structure and preparation method thereof
CN116043360A
Polymer fiber with surface concave-convex structure and preparation method thereof
CN116043362A